Unilateral branch pulmonary artery stenting in tetralogy of fallot improves ventricular function. (13th July 2021) - Bissell, MM; Mills, L; Cave, DGW; Foley, R; Greenwood, JP; Plein, S; Thomson, JDR; Bentham, JR
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NIHR Background: Pulmonary artery stenosis (PAS) occurs commonly in patients with tetralogy of fallot (ToF). Cardiac function and especially left ventricular longitudinal strain has been identified as an important prognostic factor for long term survival in ToF. The clinical relevance of unilateral PAS to long-term bi-ventricular function is poorly understood. Purpose: We sought to evaluate the effect of resolving unilateral pulmonary artery obstruction on right and left ventricular performance. Methods: We prospectively included 40 patients with TOF between 2016 and 2020, 20 who underwent unilateral PAS stenting and as comparison 20 who underwent surgical pulmonary valve replacement (PVR). MRI data was acquired during routine clinical care before and around 6-12 months after the procedure. 4 PAS patients attended additional research scans acquiring ventricular 4D flow MRI data. 4D flow MRI data was compared to the average kinetic energy curve of 10 age-matched healthy volunteers. Results: Of the 20 patients undergoing PAS, 2 also underwent percutaneous PVR and were excluded from the comparison analysis. All patients in the PAs group showed an improvement in branch PA flow differential post procedure. Patients undergoing PAS were younger than those undergoing PVR (median 12 vs 19 years, p < 0.001). Other baseline anatomical and functional parameters including right ventricular (RV) volume indexed to body surface are (RVEDV/BSA) were comparable (pre PAS median 151 [122, 170] vs pre PVR 162 [140, 191]; p = 0.217). While in the PVR group the right ventricular volumes reduced in both end-diastole and end-systole, in the PAS group RV function improved due to reduced end-systolic volume with largely stable end-diastolic volumes. Changes in the left ventricle (LV) were even more interesting. In the PVR group ejection fraction improved due to an increase in end-diastolic volume with no improvement in ventricular longitudinal strain. In contrast, in the PAS group LV ejection fraction improved by a reduction in end-systolic volume and the PAS group showed a small but significant improvement in LV longitudinal strain. In addition, ¾ patients undergoing 4D flow MRI assessment showed LV kinetic energy curve more similar to the healthy volunteer averaged  LV kinetic energy curve after PAS. The 4th patient already had a near normal LV kinetic energy curve prior to PAS. Conclusion: Unilateral PAS does not alter RV end-diastolic volumes but improves RV function. LV ejection fraction improvement is similar to that seen after PVR, but importantly PAS also improved LV longitudinal strain. This suggests that PAS might positively influence long term morbidity and mortality risk in ToF patients, but a larger multi-centre long term follow-up study is needed to confirm this.